[11C]Carboxylated Tetrazines for Facile Labeling of Trans‐Cyclooctene‐Functionalized PeptoBrushes. Issue 12 (28th December 2021) - García‐Vázquez, Rocío; Battisti, Umberto Maria; Shalgunov, Vladimir; Schäfer, Gabriela; Barz, Matthias; Herth, Matthias Manfred
Abstract: Functionalization of macromolecules (antibodies, polymers, nanoparticles) with click‐reactive groups greatly enhances the versatility of their potential applications. Click chemistry based on tetrazine – trans‐cyclooctene (TCO) ligation is especially promising and is already widely applied for pretargeted imaging and therapy. Indirect radiolabeling of TCO‐functionalized macromolecules with substoichiometric amounts of radioactive tetrazines is a convenient way to monitor the fate of those macromolecules by means of positron emission tomography (PET) imaging after their administration into the test subject. In this work, the preparation is reported of TCO‐containing graft copolymers, namely PeptoBrushes (polyglutamic acid‐graft‐polysarcosine), novel [ 11 C]carboxylated tetrazines, and their combined use in radiolabeling the polymer by inverse electron demand Diels Alder reaction, to investigate it is potential for an application in pretarget imaging or injectable brachytherapy. The procedure for [ 11 C]tetrazine production is easy and scalable, while indirect TCO‐PeptoBrushes labeling with these [ 11 C]tetrazines is mild, fast, and quantitative. This strategy allows facile 11 C‐labeling of diverse TCO‐functionalized macromolecules, so that their localization and distribution shortly after injection can be assessed by PET. Abstract : Herein, the first 11 C‐carboxylation of tetrazines is reported. These radiolabeled molecules are then clicked with a trans‐cyclooctene (TCO)‐functionalized PeptoBrushes. The procedure for [ 11 C]tetrazine production is easy and scalable, while indirect TCO‐PeptoBrushes labeling is mild, fast, and quantitative. This strategy allows facile 11 C‐labeling of diverse TCO‐functionalized theranostic macromolecules, so that their localization and distribution shortly after injection can be assessed by positron emission tomography (PET).